THE EFFECT OF EMPLOYEE PLACEMENT ON PERFORMANCE EMPLOYEES IN BARANTI DISTRICT OFFICE IN SIDERENG RAPPANG DISTRICT - SRI, SRI WIRDANA; Makmur, Mariam; Nirmasari, Dian (Universitas Ichsan Sidenreng Rappang, 2023)
This study sought to ascertain the impact of personnel placement on performance at the Gowa Branch of Baranti District. Both qualitative and quantitative data are utilised, and both primary and secondary data sources are used. 37 employees made up the study's population and sample. The technique is a combination of quantitative and qualitative descriptive analysis. Y = 0.20 + 35.124 X, where the correlation coefficient (r) is 0.37%, and the coefficient of determination (r2) is 0.1369 or 13.69%. The t-count test value is 2.21, where the t-count value is greater than the t-table value, namely 2.21 > 1.306, so it can be said that Ha is accepted and Ho is rejected. Based on the findings of the research and discussion. According to this, with 90% confidence, it is accurate that employee placement has a good and significant impact on employee performance in Baranti District, Sidenreng Rappang Regency.